PARENTING SELF EFFICACY PADA IBU YANG MEMILIKI ANAK AUTIS - Sumiati Sinaga; Istiqomah . (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Autism is a developmental disorder that is related to nerves and affects a child's ability to communicate, interact and behave. The number of children with autism in Indonesia continues to increase, including in East Kalimantan. Handling an autistic child is certainly not an easy thing for parents. The care of autistic child is very depend on the ability of parents to care for children consistently in which includes bringing their children therapy regularly. many parents become stressed because they feel unable to care for their children, and is needed support from various groups as well as families to help mothers improve their abilities and reduce stress experienced. The purpose of this study is to explore the experiences of parenting self-efficacy of mothers who have autistic children in the State SLB Pembina. This study uses qualitative research with a phenomenological approach. The participants in this study were 5 mothers who had autistic children. The data retrieval used is the purposive sampling. This study has produced two main themes, namely undergoing a care role for the condition of child abnormalities and obtaining independences in autistic children based on the beliefs in parenting. Based on the results of the study, it can be concluded that mothers who initially experience distress when they first care for their children can raise and care for their children properly. This research is expected to be a source of information in the development of nursing science and it can be used as an entry point in counseling parents regarding the experience of parents in caring for and overcoming every problems that occur in many children with autism.